Observations of the Morphological Evolution of Neuronal Intranuclear Rods in the Human Substantia Nigra Across the Age Spectrum. (11th September 2019) - Khan, Osama; Capitano, Mario; Fan, Susan; Woulfe, John
Abstract: Objectives: Parkinson's disease (PD) is a neurodegenerative disease characterized by a depletion of dopaminergic neurons in the substansia nigra (SN). Loss of SN neurons occurs at a rate of up to 10% per decade in nonpathological aging. Other age-related changes in nigral neurons include accumulation of intranuclear inclusions called Marinesco bodies (MBs). MBs have been shown to associate with a distinct type of neuronal intranuclear body called the intranuclear rod (INR). At what point in the aging process INRs develop, and when they give rise to MBs, are questions that remain unanswered. In this observational study, we set out to determine whether SN INRs display changes in their morphology across the human age spectrum. Methods: The laboratory information system was searched for hospital and forensic autopsies conducted from 2010-2017 that had midbrain sections taken. Ten slides were cut from each of 11 age groups from ages ranging from 1 month to 80 years of age. Sections were immunostained with glucocorticoid receptor (GR) to identify INRs. Results: There was a progressive age-associated transition in INR morphology from long, linear intranuclear structures in the youngest age groups (infants), to shorter linear structures at middle ages, culminating in small, dot-like juxtanucleolar structures in elderly subjects. A proportion of short INRs displayed contact with MBs in the middle age groups. Conclusion: We demonstrated a striking progressive, age-dependent alteration in INR morphology. These results suggest that INRs give rise to MBs in the SN during middle ages. As a follow-up of this preliminary observational study, quantitative analysis of INR frequency and size is currently being performed in our lab. Ultimately, we plan to expand our cases for the creation of a human SN tissue microarray, which we hope will shed light on the cellular mechanisms of neuronal ageing and degeneration in the SN.